THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN IMPLEMENTING ISLAMIC MORAL VALUES IN THE ERA OF DIGITALIZATION IN THE ENVIRONMENT OF MADRASAH TSANAWIYAH - Hujumy, Muhammad Addifaul; Khoiroh, Ummul; Khaer, Abu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to examine the role of Islamic Religious Education (PAI) in improving Islamic moral values in the era of digitalization, especially in the environment of Madrasah Tsanawiyah Nurul Jadid. With the rapid development of digital technology, new challenges have emerged for educators, including PAI teachers, in delivering material that is relevant to the times. This research uses a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation. The results of the study show that digitalization has a positive impact on PAI learning, especially through wider and faster access to information. This allows students to more easily acquire religious knowledge that is relevant to the context of the times. However, on the other hand, digitalization also poses challenges in the form of the spread of negative content that can affect student morals and behavior. In this case, PAI plays an important role in guiding students to use technology wisely, by instilling strong Islamic moral values, and providing a proper understanding of the limitations in using technology. Through PAI learning based on Islamic values, students are expected to develop a positive and responsible attitude in utilizing technology in this digital era. This research makes an important contribution in understanding the strategic role of PAI in shaping the character of superior students in the midst of technological advances